YUNON BAQTRIYA DAVLATI: SOVET DAVRI TARIXSHUNOSLIGIDA - Toirova Gulbegim Toshnazar qizi, Jumanova Kamola Ashur qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides information about the formation and rise of one of the ancient civilizations, the Greco-Bactrian state, including its history, geographical position, natural conditions, social structure, culture, rulers, disintegration, and collapse.